The Nordic Region: Can Russia ‘Divide and Rule’? Four Russo-Nordic Relations After Crimea and Trump - Mouritzen, Hans (Journal of Regional Security, 2019)
The Nordic countries interact with Russia not only in the Baltic Sea region but also in the Barents region and the Polar Arctic. In order to get a full picture of the underlying dynamics, individual Nordic Russia-relations should be studied in a comprehensive framework. The framework applied here is one of great power wedging in regional dynamics. With geopolitical differences and mutual idiosyncracies, the Nordic soil has traditionally been fertile for great powers seeking to ‘divide and rule’, and Russia has apparently succeeded since about 2000. However, in the wake of Russia’s involvement in the Ukraine conflict and the election of Donald Trump as US president, geopolitical interests seem to be converging with fairly even threat perceptions being found in Nordic capitals. This will strengthen security and defence cooperation, although a common Nordic Russia-policy is unlikely. All four countries, in particular Sweden, face difficult dilemmas in this new situation.